Evaluation and Comparison of HbA1C Level in Diabetic Patients with and without Foot Ulcer: A Case control Study - Hoseinali Danesh; Abdulbaset Maleknejad; Mohammad Aref Emami; Mahjoubeh Keykha; Alireza Bahmani (طب اورژانس ایران, 2023)
Introduction: Diabetic foot is one of the long-term microvascular complications of diabetes mellitus (DM). The prevention of foot ulcers is the most effective way to reduce severe morbidity and mortality in patients with diabetes. Appropriate glycemic control is one of the most important preventive measures for diabetic foot ulcers. Glycosylated hemoglobin (HbA1C) is representative of long-term blood glucose levels over the prior three months. The present study evaluated the relationship between HbA1C levels and the development of diabetic foot ulcers.